In vitro selective inhibitory effect of 8-hydroxyquinoline against bifidobacteria and clostridia - Novakova, Jitka; Vlkova, Eva; Bonusova, Bela; Rada, Vojtech; Kokoska, Ladislav (Anaerobe, 2013)
8-Hydroxyquinoline (8HQ) inhibited Clostridium tertium, Clostridium clostridioforme, Clostridium difficile and Clostridium perfringens in vitro with MICs of 8, 16, 32 and 32 μg/mL, respectively. In contrast, MICs of most bifidobacteria (84%) were 512 μg/mL or higher. Thus, 8HQ could be used as anti-clostridial agent or in selective media for bifidobacteria isolation.
Keywords: Microbial Sensitivity Tests; Antimicrobial activity; Feces; oxychinolin; Selectivity; mikrobiální testy citlivosti; Infant; feces; Humans; Oxyquinoline; Bifidobacterium; Anti-Bacterial Agents; lidé; 8-Quinolinol; antibakteriální látky; kojenec; Clostridium